IV. Stratigraphic Observation of the Surface Snow Cover in Mizuho Plateau, East Antarctica, 1969-1970 - ナルセ, レンジ; NARUSE, Renji (National Institute of Polar Research, 1972)
P(論文) departmental bulletin paper